Довіра в системі фундаментальних цінностей академічної доброчесності: аспект контролю навчальних досягнень студента - Гребенюк, Тетяна Володимирівна (Запоріжжя : Видавничий дім "Гельветика", 2021)
The fundamental value of trust as a core of academic integrity as an axiological construct is considered within the context of formal assessment and control of student’s academic achievements. It is stated that the matter of trust should be specifically outlined in course syllabi and other studentoriented documents regulating academic process.